Preparation of fish waste silage and its effect on the growth performance and meat quality of broiler chickens. (2nd April 2018) - Shabani, Akram; Boldaji, Fatollah; Dastar, Behrouz; Ghoorchi, Taghi; Zerehdaran, Saeed
Abstract: BACKGROUND: This experiment was conducted to evaluate the effects of replacing soybean meal with fish‐waste silage (FWS) in diets on growth performance and meat quality in broiler chickens. Fish waste (FW) was fermented with molasses and Lactobacillus plantarum and Aspergillus oryzae for 15 days. A total of 240 day‐old male Cobb 500 broiler chickens were used in a 42‐day experiment in which the birds were randomly allotted to one of five dietary treatments (containing 0, 30, 60, 90, and 120 g kg −1 FWS) in a completely randomized design. RESULTS: Results indicated that the fermentation process significantly reduced pH and ether extract, but it increased crude protein content and lactic acid bacteria count in FW. The use of FWS significantly improved daily weight gain and feed conversion ratio of broilers. The amount of thiobarbiturate‐reducing substances and lipid content in chicken's meat fed diet containing FWS was significantly lower than in the group fed a control diet. CONCLUSION: In conclusion, the microbial fermentation process is effective in improving nutritive values of FW. Feeding up to 120 g kg −1 FWS also improves the performance and meat quality of birds and can be used as a suitable protein source in broiler chickens' diet. © 2018 Society of Chemical Industry